QADARIYAH DAN JABARIYAH DI PASAR PELELANGAN IKAN BAJOE KABUPATEN BONE PROPINSI SULAWESI SELATAN - muhammad hasbi (El Harakah, 2016)
In Islamic thought, human actions are interpreted by two flow paradox. First, there is the free will view it as a human. That human actions are created his own man. It is man who wills. What he wants, he can do. Conversely, unwanted, he just biased against it. Secondly, for this group of human actions was not created by man. But by God. For this group, man can not do anything about it, humans do not have the strength to do the deed. God's man is only controlled. The first stream, in Islamic thought known as Qadariyah. While the second is called Jabariyah.